Comparing pulsed field electroporation and radiofrequency ablation for the treatment of paroxysmal atrial fibrillation: design and rationale of the BEAT PAROX-AF randomized clinical trial - Erhard, Nico; Frison, Eric; Asselineau, Julien; Aouar, Besma; Boveda, Serge; Cochet, Hubert; Deisenhofer, Isabel; Deneke, Thomas; Gimbert, Anne; Kautzner, Josef; Knecht, Sebastien; Maury, Philippe; et al. (Europace, 2024)
AIMS: Using thermal-based energy sources [radiofrequency (RF) energy/cryo energy] for catheter ablation is considered effective and safe when performing pulmonary vein isolation (PVI) in patients with paroxysmal atrial fibrillation (AF). However, treatment success remains limited and complications can occur due to the propagation of thermal energy into non-target tissues. We aim to compare pulsed field ablation (PFA) with RF ablation in terms of efficacy and safety for patients with drug-resistant paroxysmal AF. METHODS AND RESULTS: The BEAT PAROX-AF trial is a European multicentre, superiority, open-label randomized clinical trial in two parallel groups. A total of 292 participants were recruited in 9 high-volume European clinical centres in 5 countries. Patients with paroxysmal AF were randomized to PFA (FARAPULSE Endocardial Ablation System©, Boston Scientific) or RF using the CLOSE protocol with contact force sensing catheter (SmartTouch© catheter and CARTO© Biosense Webster). The primary endpoint will be the 1-year recurrence of atrial arrhythmia, and the major secondary safety endpoint will be the occurrence of acute (<7 days) procedure-related serious adverse events, or pulmonary vein stenosis, or atrio-oesophageal fistula up to 12 months. Additionally, five sub-studies investigate the effect of PFA on oesophageal safety, cerebral lesions, cardiac autonomic nervous system, durability of PVI as assessed during redo ablation procedures, and atrial and ventricular function. The study began on 27 December 2021 and concluded recruitment on 17 January 2024. Results will be available in mid-2025. CONCLUSION: The BEAT PAROX-AF trial aims to provide critical insights into the optimal treatment approach for patients with paroxysmal AF.
Keywords: recidiva; Humans; lidé středního věku; venae pulmonales; Pulmonary vein isolation; Randomized trial; Female; výsledek terapie; lidé; Atrial Fibrillation; Europe; katetrizační ablace; Radiofrequency current; ženské pohlaví; Male; Middle Aged; Pulmonary Veins; Treatment Outcome; Recurrence; mužské pohlaví; Catheter Ablation; Atrial fibrillation; Evropa; Pulsed field ablation; fibrilace síní; Catheter ablation